1990
DOI: 10.2105/ajph.80.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Lead-induced anemia: dose-response relationships and evidence for a threshold.

Abstract: We conducted a cross-sectional epidemiologic study to assess the association between blood lead level and hematocrit in 579 one to five year-old children living near a primary lead smelter in 1974. Blood lead levels ranged from 0.53 to 7.91 ,umol/L (11 to 164 ,ug/dl). To predict hematocrit as a function of blood lead level and age, we derived non-linear regression models and fit percentile curves. We used logistic regression to predict the probability of hematocrit values less than 35 per cent. We found a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
1
5

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 15 publications
3
53
1
5
Order By: Relevance
“…Moreover, the non-linear trend estimated in HCT is in agreement with the results of other studies. In particular, on the basis of their investigations, some Authors (Schwartz et al, 1990;Hense et al, 1992;Jacob et al, 2000) pointed out or hypothesised a parabolic doseresponse relationship similar to that found in this analysis.…”
Section: Haematocritsupporting
confidence: 74%
“…Moreover, the non-linear trend estimated in HCT is in agreement with the results of other studies. In particular, on the basis of their investigations, some Authors (Schwartz et al, 1990;Hense et al, 1992;Jacob et al, 2000) pointed out or hypothesised a parabolic doseresponse relationship similar to that found in this analysis.…”
Section: Haematocritsupporting
confidence: 74%
“…Still, such studies have rarely noted a threshold value of lead 48) . By applying logistic regression analyses to data of both BPb and Hct obtained from 579 children aged 1 to 5 yr, Schwartz et al reported that the probability of anemia (Hct <35%) in one-year-old children was 0% at BPb levels below 20 µg/dl, 2% at levels between 20 and 39 µg/dl, 18% at levels between 40 and 60 µg/dl, and 40% at BPb levels above 60 µg/dl 74) . The authors concluded that BPb levels close to the recommended limit value of 25 µg/dl were associated with dose-related depression of Hct in young children.…”
Section: Recent Perspective On Lead Toxicity In Childrenmentioning
confidence: 99%
“…Prior studies have focused mainly on the associations between blood lead levels and hematopoietic outcomes (13)(14)(15)(16)(17)(18), and they have demonstrated significant interindividual variation. Fewer studies have utilized measures of chelatable lead, a measure of bioavailable lead burden, and tibia lead, a measure of cumulative lead dose (19,20).…”
mentioning
confidence: 99%